2016
DOI: 10.3390/s16071079
|View full text |Cite
|
Sign up to set email alerts
|

Improved Fuzzy Logic System to Evaluate Milk Electrical Conductivity Signals from On-Line Sensors to Monitor Dairy Goat Mastitis

Abstract: The aim of this study was to develop and test a new fuzzy logic model for monitoring the udder health status (HS) of goats. The model evaluated, as input variables, the milk electrical conductivity (EC) signal, acquired on-line for each gland by a dedicated sensor, the bandwidth length and the frequency and amplitude of the first main peak of the Fourier frequency spectrum of the recorded milk EC signal. Two foremilk gland samples were collected from eight Saanen goats for six months at morning milking (lactat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
(88 reference statements)
1
9
0
1
Order By: Relevance
“…This parameter is determined by the concentration of cations and anions. As general knowledge, mastitis increases the concentration of Na + and Cl − in the milk, which then causes the electrical conductivity to rise [66]. Similar to the results obtained by studies conducted on cow milk, research on different goat breeds has shown that this indicator increases in the case of mastitis, especially when both halves of the mammary gland are affected.…”
Section: Electrical Conductivitysupporting
confidence: 70%
“…This parameter is determined by the concentration of cations and anions. As general knowledge, mastitis increases the concentration of Na + and Cl − in the milk, which then causes the electrical conductivity to rise [66]. Similar to the results obtained by studies conducted on cow milk, research on different goat breeds has shown that this indicator increases in the case of mastitis, especially when both halves of the mammary gland are affected.…”
Section: Electrical Conductivitysupporting
confidence: 70%
“…Some of these, such the somatic cell count ( SCC ), the bacteriological examination of milk samples (BAC), the DeLaval Cell Counter (DCC) or the California Mastitis Test (CMT) are laboratory analysis, or portable devices, not routinely applicable in the monitoring of animals’ health on-farm due to the costs and time requirements [ 3 ]. Others are indicators that can be evaluated at farm level, like the electrical conductivity [ 4 , 5 , 6 ] or the aspect of milk [ 7 ]. Nevertheless, these are indirect measurements of the infection and their abilities and sensitivities to detect all cases, in particular when subclinical, are not always sufficient [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The EC values in the current study were similar to those of Zaninelli et al . (2016) who reported a mean EC value of 7.64 ± 0.07 ms/cm for healthy udders/glands. The results showed higher EC values in milk of healthy udders which is due to higher temperature of milk measured for on-line electrical conductivity, as reported by Henningsson et al .…”
Section: Resultsmentioning
confidence: 99%